Pete the Cat and the Cool Cat Boogie - Dean, Kim 1969-; Dean, James 1957- (New York Harper, an imprint of HarperCollins Publishers, 2017)
Practicing a totally groovy new dance, Pete the Cat is told by a grumpy neighbor that his moves are all wrong and he resolves to become a better dancer before receiving advice from wise Owl that he will be most cool when he is just himself.
Keywords: Stories in rhyme; Cats -- Fiction; Dance -- Fiction; Animals -- Fiction; Stories in rhyme; Cats -- Fiction; Dance -- Fiction; Animals -- Fiction; Humorous fiction; Animal fiction; Realistic fiction